Freespace = Ziyou kongjian Biennale architettura 2018 - Farrell, Yvonne 1951-; McNamara, Shelley
"The Official Catalogue of the 16th International Architecture Exhibition / Biennale Architettura 2018 titled Freespace consists of two volumes: Volume I is dedicated to the International Exhibition curated by Yvonne Farrell and Shalley McNamara. The volume is divided into 3 parts. The first part is dedicated to the exhibition projects: each work is presented with 2 pages and described with texts by the curators and the participating architects accompanied by color images. In the second part, color images illustrate the projects and architectural structures with great visual impact. Third part, instead, collects in-depth texts. Volume II, on the other hand, is dedicated to National Participations, Special Projects and Collateral Events, illustrating their concepts and realizations with in-depth texts, accompanied by images, in individual contents"--Biennale di Venezia website.